Regio- and Stereoselective Multicomponent Coupling Reaction of Alkynes and Dimethylzinc Involving Allylnickelacycles - Mori, Takamichi; Nakamura, Toshiyuki; Onodera, Gen; Kimura, Masanari (Synthesis, 2012)
Nickel catalyzes the multicomponent coupling reaction of vinyl epoxides, alkynes, and dimethylzinc to provide hepta-2,5-dienyl alcohols as a mixture of E- and Z-isomers in high yields. Vinylcyclopropane participates in a similar multicomponent coupling reaction to afford dimethyl α-(hepta-2,5-dienyl)malonates with excellent E-stereoselectivity.
Keywords: nickel; multicomponent coupling; alkyne; dimethylzinc; vinyl epoxide; cyclopropane